Experimental transmission of leishmania infantum by two major vectors - Maia, Carla (2021)
We quantified Leishmania infantum parasites transmitted by natural vectors for the first time. Both L. infantum strains studied, dermotropic CUK3 and viscerotropic IMT373, developed well in Phlebotomus perniciosus and Lutzomyia longipalpis. They produced heavy late-stage infection and colonized the stomodeal valve, which is a prerequisite for successful transmission. Infected sand fly females, and especially those that transmit parasites, feed significantly longer on the host (1.5-1.8 times) than non-transmitting females. Quantitative PCR revealed that P. perniciosus harboured more CUK3 strain parasites, while in L. longipalpis the intensity of infection was higher for the IMT373 strain. However, in both sand fly species the parasite load transmitted was higher for the strain with dermal tropism (CUK3). All but one sand fly female infected by the IMT373 strain transmitted less than 600 promastigotes; in contrast, 29% of L. longipalpis and 14% of P. perniciosus infected with the CUK3 strain transmitted more than 1000 parasites. The parasite number transmitted by individual sand flies ranged from 4 up to 4.19×104 promastigotes; thus, the maximal natural dose found was still about 250 times lower than the experimental challenge dose used in previous studies. This finding emphasizes the importance of determining the natural infective dose for the development of an accurate experimental model useful for the evaluation of new drugs and vaccines.